2011
DOI: 10.1038/jp.2011.163
|View full text |Cite
|
Sign up to set email alerts
|

Neonates presenting with bloody stools and eosinophilia can progress to two different types of necrotizing enterocolitis

Abstract: Objective: We hypothesized that neonates with bloody stools and concomitant eosinophilia are likely to have atopic enteropathy rather than necrotizing enterocolitis (NEC).Study Design: This was a retrospective cross-sectional study using electronic medical records and paper charts. Records of neonates admitted to any Intermountain Healthcare NICU between 1 January 2005 and 30 June 2010 were eligible if 'bloody stools' were listed in any archive. Qualifying records were divided into two groups depending on whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 28 publications
0
12
0
5
Order By: Relevance
“…Christensen et al (30) noted eosinophilia in 54 of 275 infants (19.6%) who were evaluated for bloody stools. They hypothesized that premature infants with bloody stools and eosinophilia were likely to have atopic enteropathy and not develop the classical signs of NEC, and were therefore, more likely to have a benign course of disease.…”
Section: Eosinophiliamentioning
confidence: 99%
“…Christensen et al (30) noted eosinophilia in 54 of 275 infants (19.6%) who were evaluated for bloody stools. They hypothesized that premature infants with bloody stools and eosinophilia were likely to have atopic enteropathy and not develop the classical signs of NEC, and were therefore, more likely to have a benign course of disease.…”
Section: Eosinophiliamentioning
confidence: 99%
“…144 Christensen et al 147 noted eosinophilia in 54 of 275 infants (19.6%) who were evaluated for bloody stools. They hypothesized that premature infants with bloody stools and eosinophilia were likely to have atopic enteropathy and not develop the classical signs of NEC, and were therefore, more likely to have a benign course of disease.…”
Section: Introductionmentioning
confidence: 99%
“…1) [5, 10, 23]. Some investigators have suggested eosinophilia and bloody stools identify the onset of NEC presenting <48 hours after a blood transfusion [24], but TANEC in our infants did not necessarily have early persistent eosinophilia and/or bloody stools (table 3). In surgical specimens, the intestinal mucosa of subjects with eosinophilia and NEC had ulcers possibly related to sub-epithelial fibrosis.…”
Section: Discussionmentioning
confidence: 73%
“…Previously, researchers had proposed eosinophilia as a white blood cell-related biomarker for the onset of NEC [24]. Moreover, fibrotic disease of the gut and liver are major causes of organ injury, and today physicians have a better understanding of the pathogenesis and prevention of fibrosis [26].…”
Section: Discussionmentioning
confidence: 99%